Microsoft SQL Server 2012 certification training exam 70-462 - Cherry, Denny (InfiniteSkills, 2013)
"In this SQL Server 70-462 exam training course, expert author Denny Cherry teaches you everything you need to know to pass the Administering Microsoft SQL Server 2012 Databases Server 2012 exam. It is required that you pass the 70-462 Exam in order to earn your MCSA and MCSE certifications from Microsoft. Denny Cherry takes you through each of the topics that you will have to master in order to pass the SQL Server 2012 70-462 exam. Throughout this tutorial video, you will learn how to install and configure the SQL Server, maintain instances and databases, optimize and troubleshoot, manage data, and implement security and high availability. Each topic is broken down into step-by-step lessons, allow you to quickly learn and retain the information more effectively. Once you have completed this video based training course for the Microsoft SQL Server 70-462 exam, you will have a comprehensive understanding of how to Administer Databases with Microsoft SQL Server 2012. You will be fully prepared to write, and pass, your 70-462 exam and continue towards earning your MCSA and MCSE certifications."--Resource description page.